Analyzing The Influence of Social Media Posts on Government Policy Adoption in Papua City - Michael Rooney Gomar (Green Publisher Indonesia, 2024)
In recent years, the use of social media has been very high among millennials and the middle class in Papua. This represents a new communication channel, especially in underdeveloped areas, where the political relations between citizens and the government are mostly conducted through conventional means such as demonstrations, dialogues, public hearings, submitting open letters to the government, putting up banners, and open complaint boxes. This article aims to analyze the role of social media in the process of public policy-making in the Province of Papua. The use of social media is very high among the millennial generation in Papua to respond to local government policies. However, its influence on policy change is still limited. Only traffic management policies have changed in response to criticisms on social media. This descriptive qualitative research was conducted through interviews and document analysis. The results show that social media plays a role in voicing public aspirations but has not yet influenced policy decision-making. There is a need for political will from the Papua Local Government to integrate citizens' aspirations into public policies. Further research could formulate a model of the relationship between citizens and the government through social media for more participatory public policies.